Place of delivery and newborn care practices in Kaski district: a cross sectional study from Nepal - Acharya, Shiva Raj; Pandey, Asmi (Journal of Biomedical Sciences, 2015)
Background: First 28 days of life is known as neonatal period. Newborn care is important for the proper development and healthy life of a baby. During these days they have more risk of mortality, so special care, support and appropriate feeding is needed for healthier life. The main objective of study was to assess the place of delivery and newborn care practices in Pumdi Bhumdi VDC, Kaski, Nepal. Methods: A descriptive, cross-sectional study was carried out among 245 mothers having children aged upto 2 years in Pumdi Bhumdi, Kaski district, Nepal. Results: The mean age of mother was 24.91±3.8 years. It was found that 16.3% mother had delivery at home where as 83.7% in health facilities. After delivery, 97.1% had not applied anything on cord. The finding of study also shows that 86.1% of the newborn took bath after 24 hours and 87.3% mother feed colostrums. Place of delivery associated with education, birth order and ethnicity, but not significant with exclusive breastfeeding. Bathing was significant with education. Conclusion: Some unsafe newborn care practices exist in the community of the study area like, delivery at home, frequent visit by relatives, bathing of baby within 24 hour. There is need of education about delivery at institution and newborn care to mother and their family member. DOI: http://dx.doi.org/10.3126/jbs.v1i2.11863 Journal of Biomedical Sciences. 2014;1(2):6-11